1992
DOI: 10.1029/92je01633
|View full text |Cite
|
Sign up to set email alerts
|

Impact cratering on Venus: Physical and mechanical models

Abstract: Results are presented on laboratory, theoretical and numerical simulations of various phenomena related to impact cratering processes specific to the Venusian environment. Such processes are influenced mainly by two factors: the high atmospheric density and the high surface temperature. Model results are presented for the influence of the atmosphere on high‐velocity meteoroids, the influence of high‐velocity meteoroids on the atmosphere, the influence of atmospheric shock waves on the Venusian surface, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 14 publications
(12 reference statements)
0
16
0
Order By: Relevance
“…A number of groups have studied the disruption and destruction of bolides striking deep atmospheres (e.g., Passey and Melosh 1980, Basilevsky et al 1987, Ivanov 1988, Ivanov et al 1992, Zahnle 1992, Chyba et al 1993, Chevalier and Sarazin 1994, Boslough et al 1994, Ahrens et al 1994, Takata et al 1994, Field and Ferrara 1995, Svetsov et al 1995, Svetsov 1996, Mac Low 1996, Zahnle 1996, Crawford 1996, 1997, Roulston and Ahrens 1997. The consensus seems to be that impacting bodies of a certain size are disrupted by aerodynamic forces and that mechanical ablation (as opposed to radiative ablation, which is the usual fate of small meteors) plays a major role in the deceleration of the object as a whole (Field and Ferrara 1995, Svetsov et al 1995, Mac Low 1996, Crawford 1996.…”
Section: Overall Frameworkmentioning
confidence: 97%
“…A number of groups have studied the disruption and destruction of bolides striking deep atmospheres (e.g., Passey and Melosh 1980, Basilevsky et al 1987, Ivanov 1988, Ivanov et al 1992, Zahnle 1992, Chyba et al 1993, Chevalier and Sarazin 1994, Boslough et al 1994, Ahrens et al 1994, Takata et al 1994, Field and Ferrara 1995, Svetsov et al 1995, Svetsov 1996, Mac Low 1996, Zahnle 1996, Crawford 1996, 1997, Roulston and Ahrens 1997. The consensus seems to be that impacting bodies of a certain size are disrupted by aerodynamic forces and that mechanical ablation (as opposed to radiative ablation, which is the usual fate of small meteors) plays a major role in the deceleration of the object as a whole (Field and Ferrara 1995, Svetsov et al 1995, Mac Low 1996, Crawford 1996.…”
Section: Overall Frameworkmentioning
confidence: 97%
“…However, certain findings could be indicative: for example that an impact can lead to reduction of the gas pressure above it. Ivanov et al (1992) made a combined Russian-American study interpreting measurements by the Russian Venera probes and the American Magellan mission.…”
Section: Dependence On Ejecta Size Of Atmospheric Heating and Brakingmentioning
confidence: 99%
“…However, this simplification leads to unrealistically thin and wide projectiles and to extremely low final velocities (essentially, deceleration is inversely proportional to the projectile's thickness). Numerical models (Ivanov et al 1992;Ahrens et al 1994;Takata et al 1994;Crawford et al 1995) carried out around the same time that the pancake model was developed (i.e., the time of the collision of comet Shoemaker-Levy 9 with Jupiter) clearly showed that although flattening ("pancaking") is a typical behavior of disrupted projectiles, it is mostly restricted to a flattening factor of 1.7-2.3. Further, widening is arrested by the growth of Kelvin-Helmholtz (K-H) and Rayleigh-Taylor (R-T) instabilities and the resulting projectile fragmentation into smaller pieces.…”
Section: Separated Fragments (Sf) Model and Pancake Modelmentioning
confidence: 99%